2007
DOI: 10.1107/s0021889807000441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of side-chain length on the magnetic response of discotic metallomesogens

Abstract: The magnetic responses of columnar superstructures of discotic metallomesogens with different alkyl side-chain lengths, cobalt octa(n-alkylthio)porphyrazine (CoSx, where x is the peripheral n-alkyl chain length, x = 10, 12, 14), have been investigated by small-angle neutron scattering (SANS). CoSx (x = 10, 12, 14) were heated to their isotropic phases and cooled down to their columnar mesophases under various external magnetic fields (0.2-1.1 T) and the orientational orderings of the columnar mesophases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…[ 27] For octadecyltrichlorosilane (OTS) functionalization of Si wafer, cleaning processes were performed by 30 min sonication in 2:1 (v/v) H 2 SO 4 /H 2 O 2 , acetone, ethanol and deionized water sequentially. A cleaned Si wafer was soaked in a 4 mg mL À1 solution of OTS (90þ%, Aldrich) in toluene (Merck) and rinsed with toluene.…”
Section: Methodsmentioning
confidence: 99%
“…[ 27] For octadecyltrichlorosilane (OTS) functionalization of Si wafer, cleaning processes were performed by 30 min sonication in 2:1 (v/v) H 2 SO 4 /H 2 O 2 , acetone, ethanol and deionized water sequentially. A cleaned Si wafer was soaked in a 4 mg mL À1 solution of OTS (90þ%, Aldrich) in toluene (Merck) and rinsed with toluene.…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al studied Co complexes of symmetrical octa­(thioalkyl)­azaporphyrins 219 with Col h phases (Scheme ) and found magnetic uniaxial alignment of the columnar superstructure over a centimeter length scale via SANS measurements. , Searching for push–pull systems, which are suitable for NLO applications, Belviso et al envisaged nonsymmetrical aryl-substituted octa­(thioalkyl)­azaporphyrins 220 (Scheme ). , …”
Section: Classes Of Compoundsmentioning
confidence: 99%
“…454 Triply fused metalloporphyrin dimers 217 with peripheral alkoxy and oligoethylenglycol side chains (Scheme 96) were described by Sakurai et al 455 and found magnetic uniaxial alignment of the columnar superstructure over a centimeter length scale via SANS measurements. 116,457 Searching for push−pull systems, which are suitable for NLO applications, Belviso et al envisaged nonsymmetrical aryl-substituted octa(thioalkyl)azaporphyrins 220 (Scheme 97). 458,459 A series of derivatives 220 were prepared which assembled into Col h phases.…”
Section: Porphyrins and Tetraazaporphyrinsmentioning
confidence: 99%
“…This can make the molecules oriented, which is also a means to change the direction of the molecules [7][8][9] . What is more, Zone-Melting [10] , LB deposition [11][12][13][14] , Substrate surface treatment, IR irradiation [15][16] , magnetic [17][18] , blends. However, the use of these methods has certain limitations, and many factors need to be considered such as the solubility of the compound, the type of sacrificial layer, and the thermal stability (whether the molecular thermal temperature is higher than the liquid crystal interval).…”
Section: Introductionmentioning
confidence: 99%